The Influence of Organizational Culture, Compensation, Interpersonal Communication on Job Satisfaction In Employees of The Land and Spatial Planning Office Yogyakarta City - Lucky Bayu Nugroho; Prayekti Prayekti (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Organizational culture has a long-term impact on performance and as a major factor in determining or influencing the failure or success of an organization for the next few years. The purpose of this study is to describe (1) the influence of organizational culture on employee job satisfaction. (2) The effect of compensation on employee job satisfaction. (3) The effect of interpersonal communication on employee job satisfaction. (4) The influence of organizational culture, compensation, and interpersonal communication on employee job satisfaction. This research is a type of quantitative research, with the total population of all employees of the Yogyakarta City Land and Spatial Planning Office. The sampling technique in this study is a non-probability sampling technique where the technique used is saturated sampling (census). The number of samples in this study was 65 employees of the Yogyakarta City Land and Spatial Planning Office. The data collection technique in this study used questionnaires. The data analysis methods used in this study are validity test, reliability test, descriptive test, classical assumption test, and multiple linear regression. Data analysis is performed to identify the independent variable that affects the dependent variable. The results showed that (1) Organizational culture has a positive and significant effect on employee job satisfaction. (2) Compensation has a positive and significant effect on employee job satisfaction. (3) Interpersonal communication has a positive and significant effect on employee job satisfaction. (4) Organizational culture, compensation, and interpersonal communication simultaneously affect employee job satisfaction.